A review: protoplast isolation by using different explant / Nurul Huda Mustafa - Mustafa, Nurul Huda (Faculty of Plantation and Agrotechnology, 2016)
This review study was conducted on isolation of protoplast using A review: protoplast isolation by using different explant A review: protoplast isolation by using different explant and was focusing on different explants of major crops. It shows what types of explant is suitable and meets the preferences on demanded yield of protoplasts. Protoplast was important in regenerating and improving the traits of wanted crops with the hope of bringing benefits for the future of agrotechnology, economic and research purposes. Despite all the research conducted, still improvement and recommendations is needed to gain more successful result s in technology of culturing tissues. As for this review, the focal of view were on several types of major crops such as oil palm, paddy commodity crop such as pineapple.